Small RNA-Mediated Epigenetic Myostatin Silencing - Roberts, Thomas C (Nature Publishing Group, 2012)
Myostatin (Mstn) is a secreted growth factor that negatively regulates muscle mass and is therefore a potential pharmacological target for the treatment of muscle wasting disorders such as Duchenne muscular dystrophy. Here we describe a novel Mstn blockade approach in which small interfering RNAs (siRNAs) complementary to a promoter-associated transcript induce transcriptional gene silencing (TGS) in two differentiated mouse muscle cell lines. Silencing is sensitive to treatment with the histone deacetylase inhibitor trichostatin A, and the silent state chromatin mark H3K9me2 is enriched at the Mstn promoter following siRNA transfection, suggesting epigenetic remodeling underlies the silencing effect. These observations suggest that long-term epigenetic silencing may be feasible for Mstn and that TGS is a promising novel therapeutic strategy for the treatment of muscle wasting disorders.